Peran Artificial Intelligence dalam Pembelajaran Pendidikan Agama Kristen: Peluang, Etika, dan Tantangan - Sarah Gracia Lumbantobing; Laurenz Enjelina Siagian (REAL DIDACHE: Journal of Christian Education, 2026)
The rapid advancement of artificial intelligence has triggered paradigmatic transformations across educational sectors, including Christian Religious Education (CRE), which is inherently oriented toward holistic, relational, and transformative faith formation. However, the integration of this technology remains insufficiently grounded in an adequate pedagogical ethical framework, creating tension between digital innovation and theological values. This study aims to analyze the implications of artificial intelligence in CRE across three dimensions: pedagogical opportunities, implementation challenges, and a theologically grounded ethical framework. Employing a qualitative approach through systematic literature review and critical analysis of indexed scholarly sources, the findings reveal that artificial intelligence offers substantive opportunities for enhancing learning effectiveness, personalization, and student engagement. Nevertheless, significant challenges emerge, including the risk of spiritual reductionism, doctrinal distortion, erosion of pedagogical relationships, and digital inequality. A theological synthesis affirms that artificial intelligence must be positioned as a pedagogical instrument subordinate to the authority of faith, rather than a substitute for the teacher's irreplaceable role in character formation and spiritual development. Accordingly, a contextual and theologically-informed pedagogical ethical framework is essential to ensure that the integration of artificial intelligence genuinely supports authentic faith formation in the digital age. Keywords: artificial intelligence; challenges; Christian religious education; Opportunities; pedagogical ethics Abstrak Perkembangan kecerdasan buatan telah menghadirkan transformasi paradigmatis dalam dunia pendidikan, termasuk dalam konteks Pendidikan Agama Kristen (PAK) yang berorientasi pada pembentukan iman yang holistik, relasional, dan transformatif. Namun demikian, integrasi teknologi ini belum diimbangi dengan kerangka etika pedagogis yang memadai, sehingga memunculkan ketegangan antara inovasi digital dan nilai-nilai teologis. Penelitian ini bertujuan menganalisis implikasi kecerdasan buatan dalam PAK melalui tiga dimensi: peluang pedagogis, tantangan implementasi, dan kerangka etika berbasis teologi Kristen. Penelitian menggunakan pendekatan kualitatif dengan metode studi literatur dan analisis kritis terhadap sumber-sumber ilmiah terindeks yang relevan. Hasil penelitian menunjukkan bahwa kecerdasan buatan memberikan peluang nyata dalam peningkatan efektivitas, personalisasi, dan keterlibatan peserta didik. Namun, terdapat tantangan serius berupa potensi reduksi makna spiritual, risiko penyimpangan doktrin, degradasi relasi pedagogis, serta kesenjangan digital. Sintesis teologis menegaskan bahwa kecerdasan buatan harus diposisikan sebagai instrumen pedagogis yang berada di bawah otoritas iman, bukan sebagai pengganti peran guru dalam pembentukan karakter dan spiritualitas. Oleh karena itu, diperlukan kerangka etika pedagogis yang kontekstual dan teologis agar pemanfaatan kecerdasan buatan mendukung pembentukan iman yang autentik di era digital. Kata Kunci: etika pedagogis; kecerdasan buatan; peluang; pendidikan agama Kristen; tantangan